Safety Performance In The Aviation Industry In Kenya: The Role Of Maintenance Training - Paul Ombati Onchonga; Tonny Lukose; Gloria Muthoni (Journal of Tourism, Hospitality and Travel Management, 2025)
The aim of this study was to examine the effect of maintenance training strategies on safety performance of aviation industry in Kenya. This comes amid the growing concern over the surge of aircraft related incidences and accidents, most of which have been blamed on mechanical issues, usually associated with the maintenance operations. Specifically, the study addressed the effect of training simulators, training capacity, top-leadership support, and training frequency on safety performance of the aviation industry in Kenya. The study was anchored on dynamic capabilities theory and the human factors theory of accident causation. Using an explanatory research design, the study collected data from a sample of 175 respondents drawn from the approved aircraft maintenance organizations and domestic airlines in Kenya. The study focused on 26 aircraft maintenance organizations and 9 domestic airline companies based in Wilson Airport in Nairobi City County. The study utilized a structured questionnaire to collect primary data, where it (questionnaire) was first pilot-tested for validity and reliability. The obtained data was analysed using descriptive and inferential statistics through the statistical package for social sciences. The study findings revealed that maintenance training through training simulators, training capacity, top leadership support and training frequency significantly influenced safety performance in the aviation industry in Kenya. The study concluded that maintenance training strategies though not effectively embraced, were critical in enhancing safety performance in the aviation sector. It is therefore recommended that there is need for the stakeholders in the aviation sector to invest in maintenance training strategies such as acquisition of training simulators, improvement of training capacity, and frequently undertaking training of the maintenance personnel as a way of enhancing effectiveness of aircraft maintenance for safety performance.